2012
DOI: 10.1111/joor.12018
|View full text |Cite
|
Sign up to set email alerts
|

Practice‐based clinical evaluation of metal–ceramic and zirconia molar crowns: 3‐year results

Abstract: This practice-based study evaluates the clinical performance of conventionally luted metal-ceramic and zirconia molar crowns fabricated with pronounced anatomical core design and a prolonged cooling period of the veneering porcelain. Fifty-three patients were treated from 07/2008 until 07/2009 with either metal-ceramic crowns (MCC) (high-noble alloy + low-fusing porcelain) or zirconia crowns (Cercon System, DeguDent, Germany). Forty-nine patients (30 women/19 men) with 100 restorations (metal-ceramic: 48/zirco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 23 publications
4
40
1
2
Order By: Relevance
“…Zirconia has better mechanical properties than all of the previously introduced ceramics 3) . Furthermore, much clinical research into zirconia-based all-ceramic restorations has confirmed that zirconia ceramics exhibit high stability as a frame work material for full coverage crowns [4][5][6][7] , fixed partial dentures (FPDs) 5,[8][9][10][11] , and implant abutments [12][13][14] . It has often been reported that full-coverage zirconia ceramic restoration and FPDs might not require adhesive cementation and that they can be cemented with conventional cements, including zinc phosphate 4,6,8,11) or glass ionomer cement 5,10) .…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia has better mechanical properties than all of the previously introduced ceramics 3) . Furthermore, much clinical research into zirconia-based all-ceramic restorations has confirmed that zirconia ceramics exhibit high stability as a frame work material for full coverage crowns [4][5][6][7] , fixed partial dentures (FPDs) 5,[8][9][10][11] , and implant abutments [12][13][14] . It has often been reported that full-coverage zirconia ceramic restoration and FPDs might not require adhesive cementation and that they can be cemented with conventional cements, including zinc phosphate 4,6,8,11) or glass ionomer cement 5,10) .…”
Section: Introductionmentioning
confidence: 99%
“…19,27 Two reasons that could explain this incidence are core thickness and design. In the present study, the metal and zirconia coping were designed with even thickness.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with findings reported in several clinical studies that compared the longevity of zirconiabased and PFM crowns. 8,27 The similarity of the mechanical properties and composition of the 2 veneering materials, IPS e.max Ceram and ZirPress, could explain their comparable chipping behavior. In contrast, the void-free and stronger veneering material (LDGC) resisted chipping in CAD-on crowns for the entire length of the mechanical fatigue test.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the available literature and some short-term clinical trials, core fractures were noticeably rare reported in zirconia-based single crowns over 1 to 3 years of follow up, while the veneer fracture proportion ranged from 0% to 15% [10,11]. The incidence of chipping on zirconia based fixed restoration has been reported ranging from 0% to 4% in clinical studies with 20 to 60 months follow-up [12][13][14]. Other limitations are special Milling center is required for the scanning and processing, this phase of production is, to some degree, tedious.…”
Section: Discussionmentioning
confidence: 99%